Exact solutions to the homing problem for a Wiener process with jumps. (1st February 2021) - Lefebvre, Mario; Moutassim, Abderrazak
Abstract : We consider the problem of optimally controlling a one-dimensional Wiener process with Poissonian jumps until it leaves the interval [ a, b ] . The exact optimal control is obtained in a particular case by solving the differential-difference equation satisfied by the value function. An approximate solution is also presented in a more general case. This approximate solution is appropriate when the jump size is small.